Examining the role of regulation in the commercialisation of indigenous innovation in sub-Saharan African economies: Evidence from the Ghanaian small-scale industry - Harrison Paul Adjimah; Victor Yawo Atiase; Dennis Yao Dzansi (Administrative Sciences, 2022)
Understanding the factors that drive the successful commercialisation of indigenous innovation in Sub-Saharan African economies is still limited. From both policy and theoretical perspectives, regulation is one factor that remains crucial for the successful commercialisation of innovation. However, the empirical evidence is still unclear regarding its effect on firm performance, urging the need for more evidence from different economies, sectors, and firms. This study, therefore, examined the effects of regulation on the performance of firms engaged in the commercialisation of indigenous innovation in the Ghanaian small-scale industry, a typical low-income economy in Sub-Sahara Africa. From the frugal innovation theoretical perspective, the study assumed that firms engaged in the commercialisation of indigenous innovation in such low-income economies operate in an environment with regulatory gaps and voids. Using a sample survey of 557, it deployed PLS-SEM to test the effects of regulation on key successful commercialisation metrics. The findings show that at a 5% statistical significance level, regulation has significant positive effects on sales, employment, and owners' feelings of success. Regulation also positively moderates the influence of finance and organisational factors on overall firm performance. The study provides leading evidence of the effect of regulation on the commercialisation of indigenous innovation from Ghana and adds to the clarification of the impact of regulation. It suggests that in such low-income economies, the policy must consider more balanced and appropriate regulations, not less, or deregulating to promote indigenous innovation.
Keywords: 350; firm performance; PLS-SEM; Ghana; indigenous innovation; regulation; small-scale industry; successful commercialisation